Analisis Penyerapan Tenaga Kerja Bidang Kelautan dan Perikanan Lulusan SMK di Kalimantan Barat - Dodi; Zan Zibar; Robin Saputra; Rizqan Khairan Munandar; Hendi Santoso (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
West Kalimantan is a province surrounded by oceans, making it a potential sub-sector for the Indonesian economy. Geographically, the sea waters of West Kalimantan are located at 02O N - 03O S and 106O E - 110O E. Fishing at sea is carried out by marine fisheries households and fisheries companies domiciled in Sambas, Singkawang, Kubu Raya, Bengkayang, Mempawah, Pontianak City, Kayong Utara, and Ketapang Regencies. Based on the data obtained, it can be concluded that: most (42.60%) of vocational high school graduates in West Kalimantan in 2023 are absorbed in the workforce; most of the marine and fisheries vocational high school graduates in West Kalimantan in 2023 are working. However, there are several districts/cities whose graduates choose to become entrepreneurs and/or continue their studies. This shows that vocational high school graduates in the fisheries and marine fields in West Kalimantan can be absorbed in the workforce or continue to higher education.